New method of image steganography based on particle swarm optimization algorithm in spatial domain for high embedding capacity - Albahrey, Osamah Shihab Ahmed (Tanjong Malim, 2019)
New method of image steganography based on particle swarm optimization algorithm in spatial domain for high embedding capacity by Albahrey, Osamah Shihab Ahmed